2010
DOI: 10.1155/2010/727239
|View full text |Cite
|
Sign up to set email alerts
|

Titin-Isoform Dependence of Titin-Actin Interaction and Its Regulation by S100A1/Ca2+in Skinned Myocardium

Abstract: Titin, also known as connectin, is a large filamentous protein that greatly contributes to passive myocardial stiffness. In vitro evidence suggests that one of titin's spring elements, the PEVK, interacts with actin and that this adds a viscous component to passive stiffness. Differential splicing of titin gives rise to the stiff N2B and more compliant N2BA isoforms. Here we studied the titin-isoform dependence of titin-actin interaction and studied the bovine left atrium (BLA) that expresses mainly N2BA titin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…In-vitro motility assays (Yamasaki et al 2001; Linke et al 2002), single molecule studies (Bianco et al 2007), and myocyte mechanics (Yamasaki et al 2001) have established that the interaction between PEVK and actin retards filament sliding during systole and diastole. It has been shown that the PEVK-actin interaction is present in all cardiac isoforms and is a source of hysteresis (Fukushima et al 2010). Recently, studies using PEVK KO mice showed that the PEVK-actin interaction significantly contributes to viscosity in vivo (Chung et al 2011b).…”
Section: Viscoelasticitymentioning
confidence: 99%
“…In-vitro motility assays (Yamasaki et al 2001; Linke et al 2002), single molecule studies (Bianco et al 2007), and myocyte mechanics (Yamasaki et al 2001) have established that the interaction between PEVK and actin retards filament sliding during systole and diastole. It has been shown that the PEVK-actin interaction is present in all cardiac isoforms and is a source of hysteresis (Fukushima et al 2010). Recently, studies using PEVK KO mice showed that the PEVK-actin interaction significantly contributes to viscosity in vivo (Chung et al 2011b).…”
Section: Viscoelasticitymentioning
confidence: 99%
“…Periodically, it appears at the Z-and the M-line as well as within both the I-and A-band. [50][51][52] Within the I-band, S100A1 seems to interact with the PEVK domain of the giant protein titin in a Ca 2+ -dependent manner. 50 Titin is mainly responsible for the preservation of passive tension in CM and a single titin molecule spans half the length of a sarcomere.…”
Section: Exploring S100a1's Molecular and Cellular Biologymentioning
confidence: 99%
“…They furthermore proposed that this interaction frees the actin filaments from titin before active contraction, thereby reducing pre-contractile passive tension and facilitating initiation of contraction. 50,51 If S100A1 also interacts with titin at the A-band or with another sarcomeric protein remains to be established.…”
Section: Exploring S100a1's Molecular and Cellular Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although detailed proof of the molecular mechanism of S100A1's actions is not reported, Brinks et al speculate that they result from direct interaction of S100A1 with SR and mitochondrial proteins (i.e., RyR, SERCA, and F 1 -ATPase). Recent studies also indicate that S100A1 may enhance contractility and relaxation dynamics by regulating the interaction between the sarcomeric proteins titin and cardiac actin (13).…”
mentioning
confidence: 99%